Marketing digital y estrategias de posicionamiento de la línea posquirúrgica: caso de estudio empresa fajas renova - García Núñez, Evelyn Michelle (2025)
Digital marketing is considered as a set of information and actions that can be done in various digital media with the aim of promoting companies and products. The objective of this research was to analyze the impact of the use of digital marketing and the different brand positioning strategies implemented by “Fajas Renova”, in order to make its products known in the digital market, with a theoretical basis through different authors. The methodology developed was mixed qualitative - quantitative through the application of a survey aimed at potential consumers. As a result, it was analyzed in detail how the purchase perception strategies have influenced customers, in addition to a detailed study of the tactics used in the different digital channels to promote sales and customer loyalty and the importance of implementing effective digital marketing strategies for brand positioning within the textile area against the high rate of competition within the national and international market. Finally, it is concluded that the companies have successfully managed to gain a foothold through the different digital platforms.